Studying The Effect Of Nano-Chitosan On Inhibiting Staphylococcus Aureus Bacteria Isolated From Wounds. (Journal of the College of Basic Education, 2024)
This study were aiming to test the efficiency of Nano-chitosan in inhibiting the growth of Staphylococcus aureus bacteria, where 25 isolates were obtained from cases of wound infection, and they were obtained from the Department of Life Sciences, College of Science, Al- Mustansiriyah University, where the results showed that all bacterial isolates under study had the ability to produce biofilm and the percentage 100%, but to varying degrees in terms of the intensity of biofilm formation. The results showed that adding Nano-chitosan at rates of 2%, 04%, and 6% reduced the growth of the bacteria under study at different rates, as the highest diameter of inhibition at a concentration of 6% was (18 - 21) mm, and the diameter of inhibition at a concentration of 4% was (15 – 20) mm, while the minimum diameter of inhibition was (3-5) mm at a concentration of 2%.